Better integrating summative and formative goals in the design of next generation teacher evaluation systems - Timothy G. Ford; Kim Hewitt (Arizona State University, 2020)
In current teacher evaluation systems, the two main purposes of evaluation-accountability/goal accomplishment (summative) and professional growth/improvement (formative)-are often at odds with one another. However, they are not only compatible, but linking them within a unified teacher evaluation system may, in fact, be desirable. The challenge of the next generation of teacher evaluation systems will be to better integrate these two purposes in policy and practice. In this paper, we integrate the frameworks of Self-determination theory and Stronge's Improvement-Oriented Model for Performance Evaluation. We use this integrated framework to critically examine teacher evaluation policy in Hawaii and Washington, D.C.-two distinctly different approaches to teacher evaluation-for the purposes of identifying a set of clear recommendations for improving the design and implementation of teacher evaluation policy moving forward.